Simple area determination of strongly overlapping ion mobility peaks - Borovcová, Lucie; Hermannová, Martina; Pauk, Volodymyr; Šimek, Matěj; Havlíček, Vladimír; Lemr, Karel (Analytica chimica acta, 2017)
Coupling of ion mobility with mass spectrometry has brought new frontiers in separation and quantitation of a wide range of isobaric/isomeric compounds. Ion mobility spectrometry may separate ions possessing the identical molecular formula but having different molecular shapes. The separation space in most commercially available instruments is limited and rarely the mobility resolving power exceeds one hundred. From this perspective, new approaches allowing for extracting individual compound signals out of a more complex mixture are needed. In this work we present a new simple analytical approach based on fitting of arrival time distribution (ATD) profiles by Gaussian functions and generating of ATD functions. These ATD functions well describe even distorted ion mobility peaks of individual compounds and allow for extracting their peaks from mobilograms of mixtures. Contrary to classical integration, our approach works well with irregular overlapping peaks. Using mobilograms of standards to generate ATD functions, poorly separated compounds, e.g. isomers, with identical mass spectra representing a hard to solve task for various chemometric methods can be easily distinguished by our procedure. Alternatively ATD functions can be obtained from ATD profiles of ions unique to individual mixture components (if such ions exist) and mobilograms of standards are not required. On a set of hyaluronan-derived oligosaccharides we demonstrated excellent ATD repeatability enabling the resolution of binary mixtures, including mixtures with minor component level about 5%. Ion mobility quantitative data of isomers were confirmed by high performance liquid chromatography.
Keywords: Analysis of isomers; Ion mobility-mass spectrometry; Fitting of mobility peaks; Hyaluronan-derived oligosaccharides